TEKNIK KOLEKSI DAN PRESERVASI TUMBUHAN PEGAGAN (Centella asiatica) DI KELURAHAN TURIDA, KECAMATAN SANDUBAYA, KOTA MATARAM - Nuraini; Hendriawan; Fitriani; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Biodiversity in tropical regions requires proper documentation to support conservation and research. One important medicinal plant is pennywort (Centella asiatica), which grows in humid environments and has various pharmacological benefits. This study aims to describe the techniques of collection and preservation of Centella asiatica in the form of a dry herbarium. The research used observational and experimental methods conducted in Turida Village, Sandubaya District, Mataram City. Data were collected through field observation, direct sampling, and documentation of the herbarium process. The results showed that collection was carried out through site selection, morphological identification, complete sampling, field data recording, and temporary storage. Preservation was conducted through cleaning, arranging, pressing, drying, mounting, labeling, and storing specimens. The success of herbarium preparation is influenced by environmental, biological, and technical factors. The herbarium produced can be used as a medium for biodiversity documentation and as a reference for further research.